2003
DOI: 10.1103/physreva.67.053612
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Fermi pseudopotential: A modified Gross-Pitaevskii equation

Abstract: We present an effective potential and the corresponding modified Gross-Pitaevskii equation that account for the energy dependence of the two-body scattering amplitude through an effective-range expansion. For the ground state energy of a trapped condensate, the theory leads to what we call a shape-dependent confinement correction that improves agreements with diffusion Monte Carlo calculations. The theory illustrates, for relatively strong confinement and/or high density, how the shape dependence on atom-atom … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(98 citation statements)
references
References 32 publications
4
94
0
Order By: Relevance
“…(15), TF density (17) and the numerical results from 3D MGPE (4) by integrating the longitudinal z axis out. The results are displayed in Fig.…”
Section: Quasi-2d Bec With Hoimentioning
confidence: 99%
“…(15), TF density (17) and the numerical results from 3D MGPE (4) by integrating the longitudinal z axis out. The results are displayed in Fig.…”
Section: Quasi-2d Bec With Hoimentioning
confidence: 99%
“…For λ = 0 one finds the standard GPE (1). The contribution due to the nonvanishing size of the particles r out was found by Collin, Massignan, and Pethick [6] (for earlier work see [7]). In our case it takes the form…”
Section: Modified Gpe For δ-Functions Interactionmentioning
confidence: 79%
“…The dynamic behaviour of the three dimensional (3D) modified GP equation which take into account quantum fluctuations and the shape dependence on the interaction potential can be described by [9]  ,…”
Section: Modified Gross-pitaevskii Equationsmentioning
confidence: 99%
“…For inhomogeneous systems, recent works on two atoms in a trap have shown that the shape-independent approximation becomes less valid under strong confinement [8]. Then, a modified GP equation, which incorporates the energy dependence of the two-body scattering amplitude through an effective-range expansion has been derived [9]. To the best of our knowledge, MI in this system has not been investigated.…”
Section: Introductionmentioning
confidence: 99%